13 How to diagnose, treat and eliminate racial and ethnic disparities in our healthcare systems. (30th November 2022) - Low, Daniel
Abstract : Background: Racial and ethnic disparities exist. We can stratify processes of care and outcomes by race & ethnicity and language to identify disparities. Objectives: Identify and eliminate disparities in patients having tonsillectomy surgery. Methods: We analyzed three measures, stratified by race & ethnicity and language. Rate of prophylaxis for post-operative nausea and vomiting – PONV Rate of PONV Rate of return to the operating room with 30 days We used IHI's improvement methodology – PDSA cycles, SPC charts to close disparity gaps. Results: Black patients had a lower rate of prophylaxis at our main hospital (77%) compared to Non-Hispanic White patients (90%). At our ambulatory surgery center no disparity existed, the rate of prophylaxis 98-99% across all patients. ( figure 1A ) PONV rates were much higher in Black patients (7.3%) at our main hospital compared to Non-Hispanic White patients (3.1%). No disparity existed at our ambulatory surgery center where the rates were 1-2% for all patients. ( figure 2A ) The 30-day return to OR rate across our system was 1.4% ( figure 3A ), the funnel plots revealed disparities for Vietnamese (3.5%), Somali (2.4%) and Spanish speaking (1.8%) patients ( figure 3B ). English speaking patients had a rate of 1.3%. When stratified by race and ethnicity. We found disparities in outcomes for Asian patients (2.7%), Black patient (2.4%) and Hispanic patients (1.6%). Non-Hispanic white had a rate of 0.95% ( figure 3C ). A rapid series of PDSA cycles followed – annotated in ( figure 3A ) 98-100% of all patients now receive PONV prophylaxis ( figure 1B ). 3x reduction PONV rates for Black patients (3.6% to 1%), 6x reduction for Hispanic patients (2.4% to 0.3%). ( figure 2B ) Reduction in re-operation rate for Asian patients (2.7% to 0%). Rates for black patients and Hispanic patients are unchanged. ( figure 3B and 3C ) Conclusions and Implications: We can identify and eliminate disparities in treatment process and outcomes.